2012
DOI: 10.1371/journal.pone.0044648
|View full text |Cite
|
Sign up to set email alerts
|

Serum YKL-40 Independently Predicts Outcome after Transcatheter Arterial Chemoembolization of Hepatocellular Carcinoma

Abstract: BackgroundTranscatheter arterial chemoembolization (TACE) is the most widely used treatment option for unresectable hepatocellular carcinoma (HCC). Elevated serum YKL-40 level has been shown to predict poor prognosis in HCC patients undergoing resection. This study was designed to validate the prognostic significance of serum YKL-40 in patients with HCC undergoing TACE treatment.MethodsSerum YKL-40 level was determined by enzyme-linked immunosorbent assay. Overall survival (OS) was evaluated with the Kaplan-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…Rath et al ( 62 ) suggested that YKL-40 was a powerful fibrosis marker with high diagnostic accuracy, particularly in HCV-associated liver disease. Moreover, our results revealed that the greatest significant increase was detected in HCC patients, which was consistent with Zhu et al ( 63 ). Pelloski et al ( 64 ) suggested that serum levels of YKL-40 serve as a diagnostic and prognostic cancer biomarker.…”
Section: Discussionsupporting
confidence: 93%
“…Rath et al ( 62 ) suggested that YKL-40 was a powerful fibrosis marker with high diagnostic accuracy, particularly in HCV-associated liver disease. Moreover, our results revealed that the greatest significant increase was detected in HCC patients, which was consistent with Zhu et al ( 63 ). Pelloski et al ( 64 ) suggested that serum levels of YKL-40 serve as a diagnostic and prognostic cancer biomarker.…”
Section: Discussionsupporting
confidence: 93%
“…2 Plasma YKL-40 is high in patients with gastrointestinal, [3][4][5] breast, 6 lung, 7 prostate 8 and other cancer, [9][10][11] and is also associated with tumour burden and prognosis after a cancer diagnosis. 5,[12][13][14][15][16] Furthermore, high plasma YKL-40 predicts high risk of gastrointestinal cancer in the general population. 17 Whether YKL-40 is only a marker of inflammation and cancer or plays a causal role in the development of cancer is presently unknown.…”
mentioning
confidence: 99%
“…Elevated levels of serum YKL-40 were reported to be associated with several types of cancer, such as ovarian, esophageal, breast, lung, liver and kidney cancer (11)(12)(13)(14)(15)(16). Furthermore, high expression of YKL-40 is associated with tumor grade, poor differentiation and shorter overall survival times, and may be a potential biomarker (5,11,13).…”
Section: Discussionmentioning
confidence: 99%